A naturally occurring promoter polymorphism of the Arabidopsis FUM2 gene causes expression variation, and is associated with metabolic and growth traits. (23rd September 2016) - Riewe, David; Jeon, Hea‐Jung; Lisec, Jan; Heuermann, Marc C.; Schmeichel, Judith; Seyfarth, Monique; Meyer, Rhonda C.; Willmitzer, Lothar; Altmann, Thomas
Summary: Fumarate and malate are known intermediates of the TCA cycle, a mitochondrial metabolic pathway generating NADH for respiration. Arabidopsis thaliana and other Brassicaceae contain an additional cytosolic fumarase (FUM2) that functions in carbon assimilation and nitrogen use. Here, we report the identification of a hitherto unknown FUM2 promoter insertion/deletion (InDel) polymorphism found between the Col‐0 and C24 accessions, which also divides a large number of Arabidopsis accessions carrying either the Col‐0 or the C24 allele. The polymorphism consists of two stretches of 2.1 and 3.8 kb, which are both absent from the promotor region of Col‐0 FUM2 . By analysing mutants as well as mapping and natural populations with contrasting FUM2 alleles, the promotor insertion was linked to reduced FUM2 mRNA expression, reduced fumarase activity and reduced fumarate/malate ratio in leaves. In a large population of 174 natural accessions, the polymorphism was also found to be associated with the fumarate/malate ratio, malate and fumarate levels, and with dry weight at 15 days after sowing (DAS). The association with biomass production was confirmed in an even larger (251) accession population for dry weight at 22 DAS. The dominant Col‐0 allele that results in increased fumarate/malate ratios and enhanced biomass production is predominantly found in central/eastern European accessions, whereas the C24 type allele is prevalent on the Iberian Peninsula, west of the Rhine and in the British Isles. Our findings support the role of FUM2 in diurnal carbon storage, and point to a growth advantage of accessions carrying the FUM2 Col‐0 allele. Significance Statement: Arabidopsis thaliana and other Brassicaceae contain an additional cytosolic fumarase (FUM2) that functions in carbon assimilation and nitrogen utilization. Here, we identified a naturally occurring InDel promoter polymorphism in the FUM2 gene ( AT5G50950 ) of the European Arabidopsis population. The Insertion allele reduces FUM2 mRNA, enzyme activity and malate to fumarate conversion in natural, mapping and mutant lines and is accessionwide associated with biomass production. Our findings support FUM2 's role in diurnal carbon storage and point to a growth advantage for accessions carrying the Col‐0 FUM2 allele.